Antifungal activity of chitosan against Alternaria alternata and Colletotrichum gloeosporioides - Živković, Svetlana; Stevanović, Miloš; Đurović, Sanja; Ristić, Danijela; Stošić, Stefan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
Chitosan and its derivatives have been reported as a promising alternative for control of postharvest fungal pathogens. The objective of this study was to evaluate in vitro and in situ antifungal activity of chitosan against Alternaria alternata and Colletotrichum gloeosporioides isolated from decayed apple fruits. The fungi were tested in vitro using PDA medium with three concentrations of chitosan (1, 2 and 3 mg/ml). Fungal growth of the test pathogens was significantly affected by all chitosan doses (P<0.05) after 7 days of incubation at 25°C. Water solution of 3 mg/ml of chitosan inhibited completely the conidial germination of A. alternata and C. gloeosporioides after 18 h incubation at 25°C. The results obtained from biocontrol assay indicate that the inhibition of postharvest decay of A. alternata and C. gloeosporioides was significantly influenced by chitosan concentrations. Disease incidence in chitosan-treated fruit after 7 days incubation at 25°C was significantly lower than in the positive control for both fungi tested (P<0.05). A. alternata and C. gloeosporioides used in this study were progressively inhibited in vitro and in situ with increasing concentrations of chitosan from 1 to 3 mg/ml.